Black K-pop fan videos and polyculturalism. (2nd October 2017) - Oh, David C.
ABSTRACT: The reaction video is an understudied area in YouTube and other online scholarship. Despite its limited scholarly attention, it is an influential site of meaning making, particularly for global youth cultures. Understanding polyculturalism as the suturing of self into multiple lineages, this project argues that Black American fans self-represent their K-pop fan interests as being salient to their racial identities. The videos construct identities that are not confined to the Black–White paradigm. Instead, YouTubers engage in fan practices of production, represent conformity to values within the fan community, articulate racially specific fan participation, and express concern for racially specific marginalizing discourses. Thus, the YouTube response video becomes a complicated site with multiple negotiations that reveal the self-production of polycultural identities.